Multimedia Assisted Learning Based on Cognitive Load Theory to Enhance Capabilities Solving Linear Program in Student X TKR 1 SMK 1 Doko - Fifi Damayanti (Universitas Negeri Malang, 2014)
Pembelajaran Berbantuan Multimedia Berdasarkan Teori Beban Kognitif untuk Meningkatkan Kemampuan Menyelesaikan Masalah Program Linear Siswa X TKR 1 SMKN 1 Doko Abstract: Based on cognitive load theory, learning effective when administered instrinsic load, load germane improved, and extraneous load is reduced. Application of multimedia as an effort to achieve effective learning. This study examines the application of mathematics learning with multimedia assisted to enhance the student's ability to solve the problem of linear programming. This research is a class act consisting of two cycles. The results showed that multimedia can be used to manage the load instrinsic, improve germane, and reduce the burden of extraneous, so as to improve the ability of students to solve the problem of linear programming. Key Words: multimedia assisted learning, cognitive load theory, linear programming Abstrak: Berdasarkan teori beban kognitif, pembelajaran efektif bila beban instrinsik dikelola, beban germane ditingkatkan, dan beban extraneous dikurangi. Penerapan multimedia sebagai salah satu upaya untuk mencapai pembelajaran efektif. Penelitian ini mengkaji penerapan pembelajaran matematika dengan berbantuan multimedia untuk meningkatkan kemampuan siswa menyelesaikan masalah program linear. Penelitian ini merupakan penelitian tindakan kelas yang terdiri dari dua siklus. Hasil penelitian menunjukkan bahwa multimedia dapat digunakan untuk mengelola beban instrinsik, meningkatkan germane, dan mengurangi beban extraneous, sehingga dapat meningkatkan kemampuan siswa menyelesaikan masalah program linear. Kata kunci: pembelajaran berbantuan multimedia, teori beban kognitif, program linear